[60]Fullerene-based liquid crystals acting as acid-sensitive fluorescent probes - Pérez, Laura; Lenoble, Julie; Barberá, Joaquín; de la Cruz, Pilar; Deschenaux, Robert; Langa, Fernando (My University, 2008)
Functionalization of [60]fullerene with liquid-crystalline dendrimers and a dibutylaniline-based phenylenevinylene moiety leads to supramolecular materials, the fluorescence of which responds to acid–base stimuli.